1986
DOI: 10.1128/mcb.6.11.4039-4045.1986
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance of DNA-Mediated Transformants is Linked to Transfer of the Human mdr1 Gene

Abstract: Mouse NIH 3T3 cells were transformed to multidrug resistance with high-molecular-weight DNA from multidrug-resistant human KB carcinoma cells. The patterns of cross resistance to colchicine, vinblastine, and doxorubicin hydrochloride (Adriamycin; Adria Laboratories Inc.) of the human donor cell line and mouse recipients were similar. The multidrug-resistant human donor cell line contains amplified sequences of the mdr1 gene which are expressed at high levels. Both primary and secondary NIH 3T3 transformants co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Previous studies demonstrated that NIH 3T3 cells were rendered drug resistant after transformation with high molecular weight DNA from multidrug-resistant KB cells (Shen et al, 1986c) or by transfection with a full-length cDNA derived from the human MDR 1 gene (Ueda et al, 1987). To demonstrate that human P-glycoprotein was synthesized in these cells and that the protein produced was of the appropriate size, antibody P7 was used to immunoprecipitate labeled cell extracts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that NIH 3T3 cells were rendered drug resistant after transformation with high molecular weight DNA from multidrug-resistant KB cells (Shen et al, 1986c) or by transfection with a full-length cDNA derived from the human MDR 1 gene (Ueda et al, 1987). To demonstrate that human P-glycoprotein was synthesized in these cells and that the protein produced was of the appropriate size, antibody P7 was used to immunoprecipitate labeled cell extracts.…”
Section: Resultsmentioning
confidence: 99%
“…From the specific activity of total cell protein, the amount of P-glycoprotein (nanograms per milligram of extract) was made. ' NIFI 3T3 cells selected for multidrug resistance in colchicine have an amplified mouse mdr gene and are designated NIH-mrfr (Shen et al, 1986c). ''The MDR\ RNA expression for NIH 3T3 and NT-12 is estimated from Ueda et al (1987) and for T2C1 and NI-mrfr cells are from Shen et al (1986c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Transfections and Drug Selection. Drug-sensitive NIH3T3 cells were transfected with variants of the wildtype pHaMDR1/A (G185) retroviral vector (22,26) by the calcium phosphate coprecipitation method (27). Ten micrograms of plasmid DNA was used to transfect 3.5 × 10 5 cells/25 cm 2 tissue culture flask that were fed with fresh DMEM 3 h before transfection.…”
Section: Methodsmentioning
confidence: 99%
“…In MDR cell lines, MDRl expression is increased as a result of gene amplification or increased transcription (Fairchild etal., 1987;Fojoet al, 1985;Riordan et al, 1985;Roninson et al, 1986;Scotto et al, 1986), and overexpression of the MDRl gene, but not the MDRl gene, confers MDR (Schinkel et al, 1991). Several studies have shown that expression of either the genomic or the cDNA sequence of MDRl confers the MDR phenotype to the recipient cells (Ueda etal., 1987;Croop etal., 1987;Debenham et al, 1982;Gros et al, 1986;Shen et al, 1986;Sugimoto & Tsuruo, 1987), although the degree of resistance is generally less when compared to drug-selected MDR cells.…”
mentioning
confidence: 99%